AI-Based social media Creative Content Training to Improve MSMEs Competitiveness in The Digital Era - Inderanata, Rochmad Novian; Cahyani, Putri Dwi; Rabiman, Rabiman; Djufri, Elyas (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: Digital transformation had made social media crucial for MSME marketing, but many MSMEs had failed to adopt AI effectively due to limited digital literacy and weak branding, creating an urgent need for integrated and participatory training. Contribution: This study aimed to strengthen the creative and technical capabilities of MSMEs in utilizing AI for social media marketing, encourage intergenerational collaboration between youth and MSME owners, and propose a replicable community empowerment model based on Tri-N for sustainable digital inclusion. Method: This study used the Participatory Action Research (PAR) method, which was integrated with the teachings of Tamansiswa — Niteni, Niroke, and Nambahi (Tri N). The activities were conducted in four cyclical stages: (1) Analysis of needs and potential; (2) Technical training; (3) Discussion of content results; and (4) Evaluation and reflection for continuous improvement. Results: The results showed that digital literacy, creativity, and audience engagement had improved significantly. The project demonstrated that community-based digital training supported by relevant teaching approaches, youth-oriented content, and collaboration across generations helped small businesses grow and succeed in the online world. Conclusion: The Tri N approach contributed to helping MSMEs shift from passive digital users to active content creators by observing, emulating, and adapting AI-based strategies, resulting in sustainable digital marketing rooted in local culture and offering a replicable model for inclusive digital empowerment.